Picture and Picture Learning Model in Improving Speaking Skills Elementary School Students - Tambunan, Marlina Agkris; Sidabutar, Yanti Arasi; Panigrahi, Rashmi Ranjan; Simanjuntak, Tarida Alvina; Saadoon, Abather (Universitas Muhammadiyah Mataram, 2022)
This study was structured with the aim of improving the speaking skills of fourth grade students of elementary school by using the picture and picture learning model. This type of research is Classroom Action Research (CAR), where the teacher is the implementer of learning while the researcher is the observer. The design of this study uses the Kemmis and Mc. Taggart. The subjects of this study were fourth grade students of elementary school which consisted of 20 students. The object of research is students' speaking skills. Data collection techniques using tests and observations. Data were analyzed descriptively and presented in tabular form. The results showed an increase in students' speaking skills, the average value of speaking skills in the first cycle of the first meeting was 64.95 and the second meeting was 68.3. In the second cycle, the average value of speaking skills for the first meeting was 72.35 and the second meeting was 76.9. This means that learning in cycle II has met the indicators of success, so it can be concluded that improving speaking skills using the picture and picture learning model can improve the speaking skills of fourth grade elementary school students.